2011
DOI: 10.1038/bjc.2011.431
|View full text |Cite
|
Sign up to set email alerts
|

Host-derived MMP-13 exhibits a protective role in lung metastasis of melanoma cells by local endostatin production

Abstract: Background:Although matrix metalloproteinases (MMPs) are implicated in tumourigenesis and cancer progression, the role of MMP-13 in melanoma cell metastases is poorly understood.Methods:Lung metastases of mouse melanoma B16BL6 cells were analysed in MMP-13 knockout (KO) and wild-type (WT) mice after intravenous injection. The mRNA and protein expression of MMP-13 in lung tissues was analysed by RT–PCR, real-time PCR, immunoblotting and immunohistochemistry. The expression of SDF-1α, CXCR4 and endostatin, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Protective effects of MMPs against tumor pathology may in part account for the relative failure of MMP inhibitors as effective chemotherapeutics [46,48,49], and this concept is further supported by evidence that endogenous tissue inhibitors of matrix metalloproteinases (TIMPs) can themselves be cancer-promoters [50-53]. MMP13 in particular has widely been found to promote cancer pathology, but a few emerging reports including this one find an apparently protective role for MMP13 in cancer and other diseases under some conditions [54,55]. Moreover, there remains limited understanding of exactly how MMP-13 interactions with collagen impact tumor pathology – for example, what structural changes result from these interactions, and how do these changes promote or protect against tumor pathology?…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of MMPs against tumor pathology may in part account for the relative failure of MMP inhibitors as effective chemotherapeutics [46,48,49], and this concept is further supported by evidence that endogenous tissue inhibitors of matrix metalloproteinases (TIMPs) can themselves be cancer-promoters [50-53]. MMP13 in particular has widely been found to promote cancer pathology, but a few emerging reports including this one find an apparently protective role for MMP13 in cancer and other diseases under some conditions [54,55]. Moreover, there remains limited understanding of exactly how MMP-13 interactions with collagen impact tumor pathology – for example, what structural changes result from these interactions, and how do these changes promote or protect against tumor pathology?…”
Section: Discussionmentioning
confidence: 99%
“…The majority of matrikines, such as angiostatin, arresten, canstatin, and tumstatin, exert anti-angiogenic functions by reducing endothelial cell proliferation. Cleavage of plasminogen by MMP2, MMP3, MMP7, MMP9, MMP12, and MMP19 generates angiostatin (Patterson and Sang 1997;Cornelius et al 1998;Lijnen et al 1998;Moses and O'Reilly 2003;Brauer et al 2011), and endostatin is generated through cleavage of collagen XVIII by MMP3, MMP9, and MMP13 (Ma et al 2007;Bendrik et al 2010;Fukuda et al 2011). Besides MMPs, different cathepsin family members, including the cysteine cathepsins L and S (Felbor et al 2000;Veillard et al 2011) and the aspartic cathepsin E (Shin et al 2007), have been shown to generate endostatin from collagen XVIII.…”
Section: Angiogenesismentioning
confidence: 99%
“…MMP13 activity in chondrocytes and synovial cells appears to be critical in cartilage formation and in joint diseases (Takaishi et al, 2008). MMP13 has also been implicated in tumour invasion and metastasis (Fukuda et al, 2011;Wu et al, 2012), lung diseases (Shukla et al, 2006), and periodontal disease (de Aquino et al, 2009). Additionally, some reports suggest that MMP13 is important in IBD, an umbrella term that includes Crohn's disease and ulcerative colitis (UC), two chronic relapsing inflammatory disorders of the gut.…”
Section: Introductionmentioning
confidence: 99%